Pengaruh Kemampuan Interpersonal dan Pengalaman Magang Terhadap Kesiapan Kerja Pegawai Generasi Z di Kota Bima - Jaenab, Jaenab; Koerniawan, Iwan (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to determine whether interpersonal skills and internship experience have a positive and significant effect on the work readiness of Generation Z employees in Bima City. This study is a quantitative study. This type of research is associative with the population used in this study, namely all students who have had an internship Generation Z in Bima City. The sample used in this study was Generation Z employees in Bima City, totaling 100 final year students. The sampling technique in this study used purposive sampling based on criteria, the research instrument used was a questionnaire with a Likert scale. The analytical tool used in this study used multiple linear regression analysis using SPSS version 21. The results of this study are: 1) interpersonal skills do not have a positive and significant effect on the work readiness of Generation Z employees in Bima City. 2) internship experience has a positive and significant effect on the work readiness of Generation Z employees in Bima City. 3) interpersonal skills and internship experience have a positive and significant effect on the work readiness of Generation Z employees in Bima City.